Addressing voter suppression and disenfranchisement through electoral reforms in Zimbabwe - Fombad, Charles Manga (University of Pretoria, 2025)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2025.